Potensi Biofisik Holografi dalam Diagnosis Penyakit Seluler - Jayadi, Ismadi; Jaelani, Jaelani; Nabillah, Keyla Ratu (SEED: Journal of Scientific Research, 2025)
Biophysical holography is an innovative technology that offers unique capabilities in detecting and analyzing disease at the cellular level. This article discusses the potential applications of biophysical holography in the diagnosis of cellular diseases through non-invasive, high-resolution observation and dynamic analysis of cell structure and function. By utilizing the principle of light interference, biophysical holography is able to reconstruct three-dimensional images of cells in real-time, enabling the identification of abnormalities in cell structure and behavior, such as changes in morphology, membrane dynamics and molecular interactions. Recent research shows that this technology can support early detection of cancer, neurodegenerative disorders and pathogenic infections. Additionally, biophysical holography offers the opportunity to increase efficiency and accuracy in clinical diagnosis, while reducing the risks associated with invasive procedures. With the development of optical and computational technology, biophysical holography has great potential to become a standard method in precision medicine. Further research is needed to overcome challenges in clinical implementation, such as cost, portability, and technical validation. This article provides a comprehensive overview of the advantages, limitations, and future prospects of biophysical holography in supporting the cellular-based diagnostics revolution.